EFFECTS OF INJECTION SPEED ON MECHANICAL PROPERTIES IN HIGH-PRESSURE DIE CASTING OF MG-RE ALLOY - Kashiwabara, Y.; Ibrahim, M.D; Roslan, L.; Watanabe, H.; Sunami, Y. (mmscience, 2021)
In this study, in order to clarify the unknown physical properties of the Mg-Al-Th-RE alloy, the relationship between the injection conditions and the internal porosities and the mechanical properties exerted by the solidification microstructure were investigated. The obtained cast samples were investigated using X-ray CT internal measurements, tensile tests, Vickers hardness tests and solidification microstructure observations. The flow simulation and the X-ray CT analysis results showed that the porosity volume increased as the injection speed increases. The higher injection speed also affected the metal microstructure to become denser, which leads to a higher material strength and hardness. The eutectic phases quickly formed because of the shorter filled and cooled time. Therefore, the growth of the primary phase α-Mg was suppressed. On the other hand, it was considered that the material strength and hardness were greatly reduced by the coarse primary phase.